Virtual scanning tunneling microscopy: A local spectroscopic probe of two-dimensional electron systems - Sciambi, A.; Pelliccione, M.; Bank, S. R.; Gossard, A. C.; Goldhaber-Gordon, D. (Applied physics letters, 2010)
We propose a probe technique capable of performing local low-temperature spectroscopy on a two-dimensional electron system (2DES) in a semiconductor heterostructure. Motivated by predicted spatially-structured electron phases, the probe uses a charged metal tip to induce electrons to tunnel locally, directly below the tip, from a “probe” 2DES to a “subject” 2DES of interest. We test this concept with large-area (nonscanning) tunneling measurements, and predict a high spatial resolution and spectroscopic capability, with minimal influence on the physics in the subject 2DES.